The lLimits of restraint the military implications of a restrained U.S. grand strategy in the Asia-Pacific - Priebe, Miranda; Gunness, Kristen; Mueller, Karl P. (RAND, 2022)
In recent years, there has been growing interest among policymakers and foreign policy analysts in rethinking U.S. grand strategy, or the U.S. approach to the world. One of the most prominent alternatives to current U.S. grand strategy is a grand strategy of restraint, an approach that would define U.S. interests more narrowly, place a greater emphasis on diplomacy, reduce the size of the military and U.S. forward military presence, renegotiate or end U.S. security commitments, and raise the bar for the use of force. Advocates of restraint have broadly outlined their views, but there is a lack of detail about what a strategy of restraint would mean in practice for U.S. security policy. In this report, RAND researchers describe when the United States might use force in the Asia-Pacific region under a grand strategy of restraint, propose possible warfighting scenarios involving the defense of Japan that could guide U.S. Department of Defense planning, and describe how U.S. military posture in the region would change under such a strategy
Title from PDF document (title page; viewed March 30, 2022)
Keywords: Sicherheitspolitik; Asiatisch-Pazifischer Raum; USA; Security, International; National security / United States; United States / Foreign relations / 21st century; United States / Military policy; United States / Foreign relations / Pacific Area; Pacific Area / Foreign relations / United States; États-Unis / Relations extérieures / 21e siècle; États-Unis / Relations extérieures / Pacifique, Région du; Pacifique, Région du / Relations extérieures / États-Unis; Diplomatic relations; Military policy; National security; Pacific Area; United States; 2000-2099